Econ-art : divorcing art from science in modern economics - Szostak, Rick, 1959- (London ; Sterling, Va. : Pluto Press, 1999)
'While identifying two types of activity, namely econ-art and econ-science, he demonstrates why economists should acknowledge their artistic impulses and develop a more scientific conduct.' ARTbibliographies ModernHistorians of economic thought have long recognised the possibility that cultural influences might be important, but have never analysed them in any detail. In the first study of economics from the perspective of art history, Rick Szostak shows how the cultural influences identified by art historians have affected economic theory. He also reveals that not only has economic theory been informed by aesthetic considerations, but the very methods employed by economists are shown to serve primarily artistic goals. Professor Szostak assesses the extent of these cultural and aesthetic effects through a wide-ranging study of the development of surrealism, cubism and abstract art, juxtaposed with examples drawn from virtually every field of economics. Two types of endeavour are identified, Econ-Art and Econ-Science. Szostak argues that the pursuit of econ-science would be much aided if economists first recognised their artistic impulses, and then developed more scientific standards of conduct. As the first economist to thoroughly address the question of whether Economics is Art, Professor Szostak raises some important philosophical issues with this volume. The result is a controversial and scholarly, yet accessible, examination of the influence of both culture and aesthetic considerations on economics.
Art and Science -- Surrealism -- Cubism and More -- Mathematics as Art -- Ideology -- Econ-Art/Econ-Science -- Improving Econ-Science -- The Future of Econ-Science.
Includes bibliographical references (pages 235-248) and index.
Print version record.
JSTOR
Keywords: Economics -- Philosophy; Economics -- Methodology; Économie politique -- Philosophie; Économie politique -- Méthodologie.; BUSINESS & ECONOMICS -- Economics -- Theory; BUSINESS & ECONOMICS -- General; Economics -- Methodology; Economics -- Philosophy; Wirtschaftswissenschaften; Wissenschaft; Kunst; Economische filosofie; Methodologie; Economics; Philosophy; Art